Turning Aside to Look: Solomon Schechter and the Burning Bush - Grushcow, Lisa (Studies in Christian-Jewish Relations, 2026)
This article explores why Solomon Schechter chose the burning bush as the symbol of the Jewish Theological Seminary when he came from Cambridge to New York to lead this flagship institution in 1902. Previous explanations, including those of Schechter's contemporaries, are discussed, along with the puzzle of why Schechter himself left no record of the reasoning behind his choice. The paper then delves into a possible solution, in the form of suggested influence by Agnes Lewis and Margaret Gibson, two Scottish Presbyterian scholars who overlapped with Schechter at Cambridge. The history of the use of the burning bush emblem in the Church of Scotland, and its strong similarity to the emblem that Schechter chose for the Seminary, is discussed. The paper hypothesizes as to the significance of this religious symbol to Lewis, Gibson, and Schechter at the turn of the twentieth century, and their role not only as scholars, but also religious practitioners, committed to building their respective institutions. Finally, the relationship between these three figures is itself seen as a model for shared inquiry between Jews and Christians.